2014
DOI: 10.1007/s00429-014-0928-0
|View full text |Cite
|
Sign up to set email alerts
|

Neurotensin: revealing a novel neuromodulator circuit in the nucleus accumbens–parabrachial nucleus projection of the domestic chick

Abstract: Lower brainstem projections from nucleus accumbens (Ac) subregions to the parabrachial complex (PB), the nucleus of the solitary tract and the vagal motor nuclei have been described previously in the domestic chick by our group. Such projections, particulary those from the core and rostral pole regions of Ac have not been found in mammals or pigeons. Here we report on the presence of neurotensin (NT) in the neurons projecting from different Ac subnuclei, and also from the bed nucleus of stria terminalis, to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…For example, in mammals, the ventral pallidum receives projections from the medial and lateral shell and core, and in pigeons, it receives projections from the paratubercular region, the Stvc, and from the ventral part of the lateral MSt (Groenewegen et al, 1999; Medina and Reiner, 1997; Bálint et al, 2011). Both the avian and mammalian accumbens shell and core exhibit largely similar efferent projections, including their major projections to the ventral pallidum, basal nucleus of Meynert, nucleus of the diagonal band, lateral hypothalamus, lateral preoptic area, subthalamic nucleus, substantia nigra and parabrachial region, although a projection from neurotensin-labeled neurons in the accumbens (likely corresponding to our Stvc) and BSTL project to the parabrachial nucleus appears to be unique to birds (Bálint et al, 2011, 2016). The accumbens core and shell of both birds and mammals are distinguished by some of their afferent projections.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in mammals, the ventral pallidum receives projections from the medial and lateral shell and core, and in pigeons, it receives projections from the paratubercular region, the Stvc, and from the ventral part of the lateral MSt (Groenewegen et al, 1999; Medina and Reiner, 1997; Bálint et al, 2011). Both the avian and mammalian accumbens shell and core exhibit largely similar efferent projections, including their major projections to the ventral pallidum, basal nucleus of Meynert, nucleus of the diagonal band, lateral hypothalamus, lateral preoptic area, subthalamic nucleus, substantia nigra and parabrachial region, although a projection from neurotensin-labeled neurons in the accumbens (likely corresponding to our Stvc) and BSTL project to the parabrachial nucleus appears to be unique to birds (Bálint et al, 2011, 2016). The accumbens core and shell of both birds and mammals are distinguished by some of their afferent projections.…”
Section: Discussionmentioning
confidence: 99%
“…For the analysis of nucleus taeniae of the amygdala five sections of both hemispheres were selected from an area corresponding to the A8.8 to A6.4 of the brain atlas ( Kuenzel and Masson, 1988 ) ( Figure 2C ). To quantify c-Fos-ir cells in accumbens ( Bálint et al, 2016 ), five sections of both hemispheres were selected from A10.0 to A9.2 ( Kuenzel and Masson, 1988 ; Figure 2A ). Lateral septum was measured on five selected sections from A8.8 to A7.6 ( Kuenzel and Masson, 1988 ) in the lower half of septum starting from the ventral border of the lateral ventricle ( Figure 2B ).…”
Section: Methodsmentioning
confidence: 99%
“…Behavioural reactions to these stimuli were measured in terms of: 1) frequency of contact with the solution, 2) volume of liquid consumed, 3) frequency of head shakes and 4) beak cleaning episodes. Brain activation was measured by immunohistochemical detection of the Immediate Early Gene (IEG) product c-Fos in three interconnected subpallial brain regions: nucleus taeniae of the amygdala (TnA), nucleus accumbens (Ac) and lateral septum (LS) ( Figure 2 ) that may directly modulate taste-responsive neurons of the parabrachial complex through an anatomical pathway using neurotensin ( Bálint et al, 2011 ; Bálint et al, 2016 ), or receive gustatory information indirectly.…”
Section: Introductionmentioning
confidence: 99%
“…A similar region in starlings was also densely innervated with NT and ENK fibers and distinct from the surrounding striatum. NT immunolabel has also been identified within the ACR of chicks [Bálint et al, 2016], and similarly dense met-ENK labeling is observed in this same region in budgerigars and chickens [Reiner et al, 1984;Durand et al, 1998]. Although further characterization of NT is needed, together results suggest neurochemical homology for subdivisions of the avian and rodent NAC; see Table 2 for a summary.…”
Section: Patterns Of Immunolabeling In the Starling Nac Are Similar T...mentioning
confidence: 73%